2019
DOI: 10.1371/journal.pone.0219272
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression analysis in etiolated and de-etiolated seedlings in conifers

Abstract: Plant life cycle begins with germination of seed below the ground. This is followed by seedling’s development in the dark: skotomorphogenesis; and then a light-mediated growth: photomorphogenesis. After germination, hypocotyl grows rapidly to reach the sun, which involves elongation of shoot at the expense of root and cotyledons. Upon reaching ground level, seedling gets exposed to sunlight following a switch from the etiolated (skotomorphogenesis) to the de-etiolated (photomorphogenesis) stage, involving a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…We also found several downregulated genes in the post-blanched samples that encode AUX1, ARR-B, and SAUR. IAA1 is induced by auxin under light stress and helps in the elongation of coleoptile in rice [22]. We also found IAA1 upregulation in blanched samples, and IAA1 downregulated in the control samples.…”
Section: Plant Hormone Signal Transduction Pathwayssupporting
confidence: 65%
See 2 more Smart Citations
“…We also found several downregulated genes in the post-blanched samples that encode AUX1, ARR-B, and SAUR. IAA1 is induced by auxin under light stress and helps in the elongation of coleoptile in rice [22]. We also found IAA1 upregulation in blanched samples, and IAA1 downregulated in the control samples.…”
Section: Plant Hormone Signal Transduction Pathwayssupporting
confidence: 65%
“…Plants with repressed Lhcb1 and Lhcb2 genes are pale green and have low chlorophyll content [18,20]. The low chlorophyll content and pale color of water dropwort could be due to the downregulation of these Lhc genes [21,22].…”
Section: Blanching Affects the Light-dependent And Light-independent Reactions Of Photosynthesis In Water Dropwortmentioning
confidence: 99%
See 1 more Smart Citation
“…Gymnosperms have the ability to synthesize chlorophyll in the dark due to the presence of the three genes of light-independent protochlorophyllide oxidoreductase L, N, and B ( ChlL , ChlN , and ChlB ) involved in the light-independent reduction of protochlorophyllide to chlorophyllide [ 30 ]. This also confirms the presence of special light regulation in conifers, which makes them a unique object of research.…”
Section: Discussionmentioning
confidence: 99%
“…The features of development and metabolism in plants induced by light of different spectral composition are primarily mediated by changes in the expression of light-dependent genes [ 20 , 30 ], including those encoding chloroplast proteins, photoreceptor apoproteins, transcription factors, and enzymes involved in the biosynthesis of secondary metabolites [ 31 ] and phytohormone signaling. In our work, we showed that several genes involved in the response to RL or BL are expressed in different ways.…”
Section: Discussionmentioning
confidence: 99%